Two-step femtosecond laser etching for bulk micromachining of 4H–SiC membrane applied in pressure sensing. Issue 9 (1st May 2022) - Wang, Lukang; Zhao, You; Yang, Yu; Zhao, Yulong
Abstract: A method of two-step laser etching for bulk micromachining of 4H–SiC membranes through a femtosecond (fs) laser with a wavelength of 532 nm, a pulse width of 290 fs and a repetition rate of 100 kHz is present in this paper. Using a control variable method, the first step of fs-laser etching for rapid material removal and the second step of fs-laser etching mainly for improving surface morphology are studied by changing the laser fluence, scanning spacing, number of scans and scanning speed. The average surface roughness of the membrane bottom after the first step of laser etching is 691 nm, which is reduced to 237 nm after the second step. Compared with one-step laser etching, two-step laser etching obtains a better surface morphology, and it only takes 38% of the processing time of one-step laser etching. The finite element analysis shows that the sensitivity of the SiC pressure sensor drops with the decrease of the membrane roughness. The sensor sensitivity of the membrane fabricated by two-step laser etching is only 3.0% lower than that of the ideal smooth model. Furthermore, a 4H–SiC laser-prepared membrane with a diameter of 1.2 mm and a thickness of 75 μm applied in pressure sensor is tested, showing good linearity and repeatability at a load of up to 10 MPa.